Agony of Downtrodden Class in M. R. Anand’s Novels: Exploring the Lives of the Oppressed in Mulk Raj Anand's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Mulk Raj Anand (12 Dec. 1905—28 Sep. 2004), one of the most illustrious Indian writers in English, is famous for his portrayal of the lives of the down trodden class of the conventional Indian society. Being one of the pioneers of Indo-Anglian fiction, he along with R. K. Narayan, Ahmad Ali and Raja Rao, won the attention of the lovers of English literature and language from all over the world. He was truly a unique writer in English to gain an international leadership. Anand is particularly appreciated for his novels and short stories, which have procured the status of being exemplary works of present day Indian English literature. Essentially Indian English writing is noted for its discerning knowledge into the lives of the abused and its investigation of impoverishment, misuse and misfortune. Most of the thinkers and writers at that time were following the Marxist approach as Suresh Renjen Bald observes in case of Anand also Bald findsAnand’s works focuses on the theme of revolution as the only way to real social change for the unprivileged Indian masses. He chooses elitism, paternalism, industrialism and cooperation as the real segments in his progressive position. (473)Mulk Raj Anand was unarguably the greatest exponent of Indian writing in English. His abstract yield was injected with social and political duties and it passed on the lives of India's poor in a sensible and thoughtful way. He was impressed by the letters of Marx on India. He also took part in India’s freedom movement. He has been a co-founder of India’s greatest literary movement started in 1930. Indian literary world met a great loss with his death in 2005. The conspicuous Indian writer of novels, short stories and basic expositions in English, who is known for his reasonable and thoughtful depiction of the poor in India additionally an originator of the English language Indian novel, Mulk Raj Anand was the child of a coppersmith. Anand graduated with distinction in 1924 from Punjab University in Lahore and sought after extra examinations at the college of Cambridge and at University College in London. While in Europe, he became politically active in India’s struggle for independence and shortly thereafter wrote a series of diverse book on aspects of South Asian Culture, including Seven Little-known Birds of the inner Eye (1978), Curries and other Indian dishes (1932), Persian Painting (1930), The Hindu view of Art (1933), and The Indian Theatre (1950). (Britannica)